Beyond the amusement, puzzlement and challenges: an enquiry into international students' academic acculturation. Issue 12 (1st December 2016) - Elliot, Dely Lazarte; Reid, Kate; Baumfield, Vivienne
Abstract : This paper investigates the phenomenological experiences of academic acculturation of selected non-British post-doctoral academics with a retrospective focus on their experiences as PhD students. The participants came from different disciplines and countries of origin to pursue several years of postgraduate research in different British higher education institutions. The typical, yet distinct, experiences of an exceptional group of early career academics offer invaluable insight into the joys, excitement, puzzlement and challenges that international students often encounter as they embark on studying and living in a foreign country such as the UK. Using Urie Bronfenbrenner's bio-ecological theory of human development, our paper presents a theoretical perspective that can help elucidate and offer a greater understanding of what appear to be complex incidences in international students' experiences. These incidences can, arguably, be crucial to the success or failure of students' sojourns.